The Effect Of Work Culture, Service Quality And Job Satisfaction On Employee Performance At The Civil Service Police Unit, Buleleng Regency - I Putu Agus Adnyana; Ni Made Widi Sarining (UNIVED Press, 2026)
This study was conducted with the aim of finding out how the existing work culture can affect performance, good service quality from each employee can help improve performance and job satisfaction from each individual who works can affect employee performance. The analysis technique in the study by knowing the value of each research instrument, be it validity test, reliability test, classical assumption test, multiple linear regression analysis, model feasibility test (Goodness Of Fit), hypothesis test. The research that has been done shows the impact of a good work culture can change the performance produced by employees, from the existence of a good work culture it will certainly help employees in maximizing performance. Good service quality to the agency has an effect on the performance results of each individual who works, from the results of the study it can be said that good service quality from each employee can affect performance. Job satisfaction from each employee or individual in working has a positive impact on the results of employee work, good satisfaction can affect the performance of an employee who works.